Imports, status preference, and foreign borrowing - Walter H. Fisher (Institute for Advanced Studies (IHS), 2004)
This paper considers the implications of consumption and borrowing externalities in a small open economy framework. The former reflect the assumption that status conscious agents care about the relative consumption of imported goods, while the latter arise because agents do not take into account the effects of their borrowing decisions on the interest rate on debt. We analyze in the paper the impact of an increase in the degree of status preference on the saddlepath adjustment of the decentralized economy. In addition, the contrasting steadystate and dynamic properties of the social planner's economy are derived, along with the corresponding optimal tax and subsidy policies.
Keywords: E21; F41; 330; imports; status-preference; current account dynamics; Kleines-offenes-Land; Import; Internationaler Kredit; Öffentliche Schulden; Zins; Leistungsbilanz; Theorie